Platelet RNA in Cancer Diagnostics - Tjon-Kon-Fat, Lee-Ann; Sol, Nik; Wurdinger, Thomas; Nilsson, R. Jonas A. (Seminars in Thrombosis and Hemostasis, 2018)
Platelets are involved in several steps of cancer metastasis. During this process, platelets are exposed to the tumor and its environment, thereby exchanging biomolecules with the tumor cells and resulting in tumor-mediated “education” of the platelets and a change in their RNA profile. Analysis of platelet RNA profiles or direct measurement of tumor-derived biomarkers within platelets can provide information on ongoing cancer-related processes in the individual (e.g., whether the patient has cancer, the tumor type, and possibly identify oncogenic alterations driving the disease for treatment selection). The close interaction with the disease process and the ability to respond to systemic alterations make platelets an interesting biosource for implementation in precision medicine.
Keywords: platelets; biomarkers; liquid biopsy